Economic considerations to decide on the prices of buffalo steer in performance testing, according to their individual economic merit - Fraga, L. M.; Cino, Delia M.; López, O. (Cuban Journal of Agricultural Science, 2022)
Information from performance testing of Buffalypso x Carabao crossbred buffaloes, from a genetics enterprise in Cuba, was used. The information comprised the interval from 2011 to 2018, and corresponded to the weight at weaning (8 months) and the final live weight of the test (18 months of age), their breeding values and a selection index that combined both characteristics. The cost sheet of buffalo activity of the enterprise was made, with regard to performance testing. Individual benefit or individual economic merit was determined using two sales prices: 11.20 and 6.40 Cuban pesos/kg of final live weight. Proposals for steer prices were made at the end of the performance testing, according to individual economic merit. Three different calculation methods were used. Data processing was carried out using SAS 2013. Multiple regressions were obtained between benefits and individual breeding values, as well as with the selection index, from the consideration of the two prices. The linearity that exists between the benefits and the breeding values that justify the selection of animals with greater merit was showed, as well as the usefulness of the evaluation by index. Higher values were associated with higher benefits, particularly when the higher price per kilogram of live weight was used. The importance of evaluating steers in performance testing for individual benefit was highlighted, and it was considered that their sale prices should be associated with their final live weight, breeding values and accuracy of the index used to determine individual economic merit. Key words: prices, benefit, breeding value, indices, steers, buffaloes